Water Evolution in Direct Methanol Fuel Cell Cathodes Studied by Synchrotron X‐Ray Radiography. Issue 3 (30th April 2013) - Schröder, A.; Wippermann, K.; Arlt, T.; Sanders, T.; Baumhöfer, T.; Markötter, H.; Mergel, J.; Lehnert, W.; Stolten, D.; Manke, I.; Banhart, J.
Abstract Water evolution, distribution, and removal in the cathodes of a running direct methanol fuel cell were investigated by means of synchrotron X‐ray radiography. Radiographs with a spatial resolution of around 5 μm were taken every 5 s. Special cell designs allowing for through‐plane and in‐plane viewing were developed, featuring two mirror‐symmetrical flow field structures consisting of one channel with the through‐plane design. Evolution and discharge of water droplets and the occurrence of water accumulations in selected regions of the channels were investigated. These measurements revealed a nonuniform distribution of water in the channels. Both irregular and periodic formation of water droplets were observed. In‐plane measurements revealed, that the droplets evolve between adjacent carbon fiber bundles of the gas diffusion layer. The water distribution within the channel cross‐section fits very well to the pressure difference between cathode channel inlet and outlet. The quick discharge of water droplets causes sudden decreases of the pressure difference up to 4.5 mbar.